(3LRA ef GdCQHYhf MOjkKG aj aVd GdUdGI Ydi GdfHis - (3CMeO Hf Ydj Hf CMeO GdaRGQj GdbGgQj GdbdbTfOj , TgGH GdOjf, CHh GdYHGS, J (B821 (3g` s
(3ChdgG (B:s
(3hHYO adeG cGfJ GdUdGI Ydi GdfHi Udi Gddg Ydjg hSde JZaQ GdPfhH GdSGdaI hJLF jhe ddCRaI aGSJNQJ Gdgd JYGdi hNQLJ GQHYjf MOjKkG ef GdGKGQ GdeNJUI HaVd GdUdGI Ydi GdfHi GdeNJGQ s
(3BNQgG (B:s
(3GdMOjK Gdehai GdGQHYjf Yf GfS Hf eGdc QVi Gddg Yfg bGd bGd QShd Gdgd Udi Gddg Ydjg hSde (B:( (3EPG cf jhe GdbjGeI jLF CUMGH GdMOjK heYge GdeMGHQh dMHQge Xdhf jahM ajbhd Gddg YR hLd dge CfJe CUMGH GdMOjK WGd eG cfJe JUdhf Ydi GdfHi Udi Gddg Ydjg hSds
(3HgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3JNQjL s
(3eUOQ GbJfGA GdCUd (B:s
(3ShgGL (B_ (3eUQ (B((3MOjK (B62) s
Keywords: (3GdMOjK h GdeUWdMs